2013
DOI: 10.1103/physreva.88.043413
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-wave-packet quantum interference in the intense laser dissociation of the D2+molecule

Abstract: Recently it has been recognized that electronic conical intersections in molecular systems can be induced by laser light even in diatomics. As is known a direct consequence of these accidental degeneracies is the appearance of nonadiabatic effects which has a strong impact on the nuclear quantum dynamics. Studying the photodissociation process of the D 2 + molecule, we report here some observable quantum interference phenomena that arise from the topological singularity induced by a strong laser field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…A wealth of nuclear-wave-packet quantum interferences show up in intense laser dissociation due to the nonadiabatic involvement of the rotation [8,9]. A robust effect in the angular distribution of the photofragments has been found that serves as a direct signature of the LICI and should be amenable to observations [10].…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of nuclear-wave-packet quantum interferences show up in intense laser dissociation due to the nonadiabatic involvement of the rotation [8,9]. A robust effect in the angular distribution of the photofragments has been found that serves as a direct signature of the LICI and should be amenable to observations [10].…”
Section: Introductionmentioning
confidence: 99%
“…A signature of LICI's is quantum interference in strong-field laser-induced dissociation of the hydrogen or deuterium molecular ion [18,19]. Calculations predict that the interference produces modulations of the angular distributions of the dissociated fragments.…”
mentioning
confidence: 99%
“…In the framework of this model, we have followed the nuclear motion on electronic potential energy surfaces which have an important role in the dynamics. We have extended an existing approach [10][11][12][13][14][15][16][17] which considered only bound electronic states in the dynamics by including the potential energy surfaces corresponding to ionized states. This way, beside the dissociation we were also able to study the ionization.…”
Section: Discussionmentioning
confidence: 99%
“…A few years ago, we have started a systematic study of the nonadiabatic effect induced by laser fields in molecular systems and demonstrated that the light-induced conical intersections have a significant impact on several dynamical properties (like the molecular spectra, the molecular alignment etc.) of diatomic molecules [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%